DETERMINAN KEBIJAKAN BELANJA PEMERINTAH DAERAH KABUPATEN OGAN ILIR - Ikhsan, Addinul; Romli, Harsi; Zamzam, Fakhry (Jurnal Ecoment Global, 2020)
Â This study aims to determine what factors influence the spending policy of the Ogan Ilir district government. The independent factors in this study are Regional Taxes (X1), Regional Retribution Variables (X2), Separated Regional Assets Result Variables (X3) and Other Variables Legal Original Regional Income (X4), while the dependent factor is Regional Expenditure (Y The analysis was carried out with multiple linear regressions The results of this study were Regional Taxes (X1), Regional Retribution (X2) Separated Regional Assets (X3) Other Legitimate Original Regional Income (X4) simultaneously affected district government spending. Ogn Ilir.Local Taxes (X1), Retribution (X2) Separated Regional Wealth (X3) Other Legitimate Original Revenue (X4) has a partial effect on the local government of Ogan Ilir Regency.Â Keywords: Local Taxes, Regional Retributions, Separated Regional Assets, Other Legitimate Regional Original Revenues, Regional Expenditures